To study the prescription pattern of antibiotics in medicine intensive care unit at tertiary care hospital - Naikwadi, Imran B.; Baig, Shiraz Mirza; Bhattacharya, Meenakshi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug utilization studies are crucial and create a positive awareness about proper use of drugs. Analysing the pattern of prescriptions is important in the settings of intensive care units where patients receive multiple antibiotics. The objective of this study was to analyse the use of antibiotics in a Medicine Intensive Care Unit (MICU) of Government Medical College and Hospital, Aurangabad, Maharashtra, India, a tertiary health care centre. Methods: Total 988 number of patients admitted in MICU from January 2017 to June 2018 were enrolled in the study and fulfilling inclusion criteria. Demographic details, disease state and prescription of antibiotic was recorded. Results: Out of 988, n=700 patients received antibiotics. Most common diseases for which patients were admitted in MICU included OP poisoning (24.86%), snake bite (15.14%), bilateral pneumonitis (12.71%), HELLP syndrome (12.14%), and the least common conditions were chronic obstructive pulmonary disease (COPD), meningitis, sepsis with multiple organ dysfunction syndrome (MODS), Guillen barre syndrome (GBS), lung abscess etc., Most common single antibiotic used in the studied cases was ceftriaxone (21.42%) followed by either alone or in combination piperacillin and tazobactam (12.04%), metronidazole (11.85%) etc. Conclusions: Total 700 patients received systemic antibiotics in present study bringing the incidence of systemic antibiotics use in MICU to be 70.85%. Ceftriaxone and combination of piperacillin and tazobactam are most commonly used antibiotics in MICU of the hospital. All patients admitted in this MICU received antibiotics as per the standard protocols of the hospital.